Memetic commemorations: remixing far-right values in digital spheres. Issue 16 (10th December 2021) - Trillò, Tommaso; Shifman, Limor
ABSTRACT: This paper examines memetic content as a window into the values expressed by far-right constituents. Our main premise was that far-right memes are a site of interaction between two types of values: those of the far-right as a social movement and those characterizing memetic communication on social media. We studied this notion through a case from Italy: the photo-based meme genre of 'alternative calendar commemorations' that memorialize events or figures important to the far-right imaginary. A multi-modal qualitative analysis based on Schwartz's theory of personal and political values yielded mixed results. As expected, we found strong appeals to collectivistic values such as patriotism and tradition. Yet some of the individualistic values associated with memes, such as self-direction and authenticity, were also evident in the corpus. We conclude by discussing how this blend of values challenges both well-established value theories and perceptions about the political work of far-right memes.